Present status and approach for sustainable management of riverine fisheries of Nigeria - Olopade, Olaniyi Alaba; Dienye, Henry Eyina (Journal of the Inland Fisheries Society of India, 2021)
Nigeria has many rivers spread all over the country providing important goods and services to the people, including fisheries. The rivers are also used forseveral other purposes that require better management of these vast resources to increase fish production. This paper briefly highlights: i) the extent of river systems; ii) potential and production from river fisheries; iii) fish production of Nigeria during 2006–2015; iv) characteristics of river fisheries; v) problems faced by the riverine fisheries and legal regulatory regime and management of river fisheries in Nigeria. The data used were from published information on the riverine fisheries in Nigeria and the role of government in the managementof the resources. The river systems have heterogeneity of many fish species of commercial importance with little or no management measures in place to protect the resources due to open access nature and weak and ineffective fisheries regulations. The paper suggests a new framework for management of river fisheries. The new approach recognizes that effectiveness of the riverfisheries management relies on the integration of all river management agencies in Nigeria and the formulation and implementation of holistic management policies. Measures such as the fish stock enhancements, river restoration and use of effective regulations with community involvement should be given adequate attention.Key words River, Inland fisheries, Regulations, Management, Nigeria